(untitled) (American Journal of Islam and Society, 1998)
What is reality? Is reality what we see? How do we tell what is real, and how do we differentiate “real” from “false” or uncover the truth in an objective fashion? The search for reality or understanding the dynamics of human interaction in an institutionalized setting has resulted in a vibrant debate in international relations (IR) theory over the metatheoretical foundations of knowledge production. Positivists and realists claim that truth and reality can be and have been uncovered by thorough and patient research. Truth is, after all, “out there” somewhere in the real world, and it is the task of social scientists to uncover it. Critical social theorists, however, argue that social science is not akin to physical or even natural sciences, for human behavior is dynamic and varies both spatially and temporally. “Reality” or “truth” can never be discovered or known completely because of the nature of social activity. Furthermore, there are no fixed foundations for judging what is “real,” “true,” or “false.” Hence, the attention of critical social inquiry has focused predominantly on the epistemological and ontological foundations of social scientific methods. By concentrating on epistemology and ontology, critical social theorists have shown the structural weakness of positivist and realist theories. Furthermore, the inability of positive social science to go beyond surface structures to explore deep structures of knowledge also has been exposed by critical social theorists. The unequivocal outcome of critical social theory is that knowledge, interest, and preference matter and, therefore, cannot be assumed. The critical social theorist does not focus on the cognitive manifestations of knowledge, interests, and preferences, but rather on how they are formed, created, or constructed. However, despite its ombudsman-like value and importance, critical social theory has yet to emerge as an effective alternative to positive social science. Critical social theory has remained true to its name and has continued to play the role of a harsh but valuable critic. Keyman seeks to buck this trend by providing a basis for using critical social theory not just as an epistemological critique to challenge the extant theoretical hegemony, but also to deploy it as a “first-order theorizing tool”-an ambitious goal indeed. His book is an attempt to bridge the theory-metatheory gap found in IR theory and, at the same time, elevate critical social theory to the level of such first-order theories as the much maligned Waltzian theory of international relations. The challenge of deploying critical social theory not just as a captious force, but rather as a constructive theory, is a difficult and slippery task. Critical social theory should be able to criticize and dismantle without relying on foundational support (i.e., without relying on positivistic moments). In addition, it also should resist succumbing to the temptation of assuming the discourse of the hegemon, in which the “other” becomes the subject. Keyman attempts to traverse these intellectual minefields by emphasizing the need for dialogical interaction between discourse (object) and subject. The object and subject should ...